ENERGY DISTRIBUTION IN THE ALTERNATIVE JET FUEL PRODUCTION AND COMBUSTION PROCESS - Y. S. Kirdyushkin (Научный вестник МГТУ ГА)
This article presents an algorithms to energy balance equations generation describing the process of hydrocarbon compounds production, as well as provides an assessment of alternative jet fuel application necessity. Based on the proposed model for calculating the energy distribution for jet fuel production process from renewable energy sources (biomass) a rational choice of the most suitable alternative types of aviation fuel becomes possible